Preclinical evaluation of uPAR-ICG-FVIOs for dual-mode imaging and magnetic hyperthermia therapy in pancreatic cancer - Luo, Tao; Zhang, Kelan; Wu, Chong; Wu, Xiaolong; Yang, Haojie; Chen, Zhigang; Jiang, Fen (Frontiers in Pharmacology, 2025)
BackgroundThis study presents a novel targeted nanomedicine for pancreatic cancer imaging and local magnetic hyperthermia therapy (MHT): urokinase plasminogen activator receptor (uPAR)-targeted, indocyanine green (ICG)-conjugated ferrimagnetic vortex iron oxide (FVIOs) nanorings (u-I-FVIOs). uPAR is a cancer-selective membrane protein, ICG is a clinically approved near-infrared (NIR) dye, and FVIOs are well-characterized nanorings with high efficiency in heat conversion under alternating magnetic field (AMF).Methods & ResultsWe systematically evaluated the physicochemical and biological properties of u-I-FVIOs and demonstrated their tumor targeting capacity and AMF-dependent cancer cytotoxicity. Following intravenous (I.V.) administration, u-I-FVIOs produced robust fluorescence and MRI signals in tumors, achieving a tumor-to-background ratio of 3.5–4.5 at 12–24 h post-injection, compared with 2.5–3.0 for I-FVIOs and 1.5–2.5 for the ICG group. In a PANC-1 subcutaneous pancreatic tumor mouse model, animals received one of four treatments: Blank, Blank + AMF, u-I-FVIOs, or u-I-FVIOs + AMF. The Blank and u-I-FVIOs were administered intratumorally (I.T.), AMF exposure was applied for 600 s after the I.T. injections. u-I-FVIOs + AMF resulted in near-complete tumor regression (tumor suppression rate: 93%; mixed-effects model: P = 0.0001) and significantly prolonged survival (Log-rank test: HR = 0.12, P = 0.009) compared to the Blank control group. In contrast, the u-I-FVIOs–only group showed no antitumor effect or survival benefit. Notably, no systemic toxicity was observed in either u-I-FVIOs treatment group.ConclusionThis study presents the first theranostic applications of u-I-FVIOs, highlighting their potential as a dual-mode imaging and targeted MHT agent for pancreatic cancer.